PENDIDIKAN ANTI KORUPSI BAGI SISWA SEKOLAH DASAR DI KECAMATAN GUNUNGPATI - Oktaviani Adhi; Suciptaningsih Suciptaningsih (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2014)
Schools can take a strategic role in the implementation of anti-corruption education, especially in a culture of anti-corruption behavior among students. This study has the objective to know the anti-corruption education for elementary school students in the Kecamatan Gunungpati. This research was conducted using qualitative methods, descriptive analytical. Data collection techniques used were interviews, observation and documents. Analysis of data using qualitative research phases according to Spradley. While in checking the validity of the data using a data triangulation techniques. The results showed that the implementation of anti-corruption education for elementary school students in the Kecamatan Gunungpati divided into two strategies that are inclusive (inserted in various subjects) and exclusive (extracurricular student). Implementation of anti-corruption education for elementary students in the Kecamatan Gunungpati have not been maximized due to various constraints, such that not all teachers follow the dissemination of anti-corruption education so have limited knowledge about planting and how effective anti-corruption education and efficient for elementary students and the lack of facilities and infrastructure supporters of anti-corruption education for students in elementary school. The impact of the implementation of anti-corruption education for elementary school students is increasing student achievement both in the classroom and outside the classroom, because students are accustomed to being kind, including honest, disciplined, caring, brave, responsible, and so forth. The conclusion is that the implementation of anti-corruption education should be internalized to the students at an early age in order to get used to conduct anti-corruption measures. Required examples from various sides for maximum results.?é?á